2017
DOI: 10.1007/s40520-017-0888-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between masticatory function and frailty in community-dwelling Japanese elderly

Abstract: All three masticatory functions (maximum occlusal force, mixing ability, and self-reported chewing ability) were associated with pre-frailty or frailty in community-dwelling Japanese elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 27 publications
6
28
1
Order By: Relevance
“…Although a cross‐sectional study reported that both grip strength and occlusal force were associated with frailty, no such relationships were observed in the present study. This difference may have resulted from the high ratio (about 70%) of participants whose status changed from robust to pre‐frail in the worsening group (ie, who were in the early stage of frailty progression).…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Although a cross‐sectional study reported that both grip strength and occlusal force were associated with frailty, no such relationships were observed in the present study. This difference may have resulted from the high ratio (about 70%) of participants whose status changed from robust to pre‐frail in the worsening group (ie, who were in the early stage of frailty progression).…”
Section: Discussioncontrasting
confidence: 95%
“…We previously reported an association between frailty and masticatory function in a cross‐sectional study of 2014 data; however, a causal relationship could not be confirmed because that study was cross‐sectional. Thus, in this study, we evaluated frailty in the same subjects over a 2‐year period and found that masticatory ability was related to the progression of frailty.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the experimental group obtained larger values of X 50 , which indicates worse MP. Although there are no studies evaluating MP in frail elderly people using the sieving method, our finding is in agreement with the results of Horibe et al ,. who verified that the mixing ability, evaluated by a colour‐changeable gum, was associated with frailty in a community‐dwelling Japanese elderly population.…”
Section: Discussionsupporting
confidence: 93%